Produits de terroir ou système agricole ? Patrimonialisation de l’alimentation en Amazonie brésilienne - Esther Katz; Lucia Hussak van Velthem (In Situ)
The Amerindians of the northwestern Brazilian Amazon cultivate a large variety of plants. Bitter cassava is the key species, with over a hundred varieties. By complex processing, these plants are transformed into tasty dishes. In a context of urbanisation, progressing now for over thirty years, industrial food products are now competing with local agricultural products. We first thought of promoting local products of the terroir, but wondered after all whether this was relevant in a multi-ethnic context where people share their knowledge, practice subsistence agriculture and have no traditions of trade. Following the requests of the local Amerindian associations, our collaborative research finally led to the designation as heritage, by the Brazilian Institute of the National Historical and Artistic Heritage, of the regional agricultural system, including the food system and its associated material culture. The aim of this article is to describe the process that led to this recognition as heritage and the ideas around the definition of food heritage. Its objective is also to show the difficulty of isolating cassava from the agricultural and food system as a whole, hence the choice to see a system rather than a single product as heritage.